Prevalence, incidence and clinical impact of cachexia: facts and numbers—update 2014. Issue 4 (11th November 2014) - von Haehling, Stephan; Anker, Stefan D.
Abstract : Cachexia is a serious but underrecognised consequence of many chronic diseases. Its prevalence ranges from 5–15 % in end‐stage chronic heart failure to 50–80 % in advanced cancer. Cachexia is also part of the terminal course of many patients with chronic kidney disease, chronic obstructive pulmonary disease (COPD) and rheumatoid arthritis. Mortality rates of patients with cachexia range from 10–15 % per year in COPD through 20–30 % per year in chronic heart failure and chronic kidney disease to 80 % in cancer. The condition is also associated with poor quality of life. In the industrialised world, the overall prevalence of cachexia (due to any disease and not necessarily associated with hospital admission) is growing and it currently affects around 1 % of the patient population, i.e. around 9 million people. It is also a significant health problem in other parts of the globe. Recently there have been advances in our understanding of the multifactorial nature of the condition, and particularly of the role of inflammatory mediators and the imbalance of anabolism and catabolism. Several promising approaches to treatment have failed to live up to the challenge of phase III clinical trials, but the ghrelin receptor agonist anamorelin seems to have fulfilled at least some early promise. Further advances are urgently needed.